Poimenovanja Turkov in muslimanov pri Trubarju in drugih protestantskih piscih 16. stoletja - Jelovšek, Alenka (Slavia Centralis, 2020)
The expressions used for Turks and Muslims in the works of Trubar and other 16th century Slovene Protestant writers The article presents the expressions denoting Turks and Muslims in the works of Slovene Protestant writers in the 16th Century. The meanings of the ethnonym Turks and adjective/ adverb Turkish that often went beyond the ethnic denomination and were also used for denoting adherence to Islam or in the sense ‘heretical’ or ‘infidel’ are defined and pejorativeor expressive descriptions of Muslims used by the authors are presented, as well as ethnonyms Saracens, Arabs and Moors. In the second part of the article, pejorative or expressive descriptions of Muslims used by the authors are presented; when relevant, the used expressions are compared with those in German original texts. The difference according to the language and the addressee of a particular text and the propagandistic function of pejorative designations are highlighted; their use is compared with the use of similar expressions in selected archive documents of the Landstände in Carniola that corroborates that expressive descriptions of Turks are predominantly used in texts intended for addressees physically removed from the Turkish threat.